Pelatihan Patient Centered Care pada Mahasiswa Kesehatan sebagai Upaya Menurunkan Tingkat Nyeri Perineum Ibu Post Partum - Sulistianto, Henri; Maretta, Megayana Yessy; Andhikatias, Yunia Renny; Astuti, Hutari Puji (Jurnal Pemberdayaan Umat, 2024)
Purpose: This community service activity aims to improve the knowledge and skills of health students about Patient Centered Care (PCC) as an effort to reduce the level of postpartum maternal pain. Methodology: This community service activity was carried out on health students who were practicing at RSUD Ibu Fatmawati Soekarno in Surakarta City. This activity was carried out through several stages, namely pretest, education, demonstration, and posttest. Results: The results of the community service show that students experienced an average increase in knowledge of 85.33% and an average increase in PCC practice of 76.22%. Limitations: Community service activities are carried out targeting health students in 1 practice area. Health students who were practicing at the time the activity was carried out were the targets of this community service activity, namely midwifery and nursing students. While other health students were not involved because they were not practicing at the time the activity took place Contribution: This community service activity can be an alternative in improving the knowledge and skills of Patient Centered Care of students who are prospective health service providers in the future.